State responses to biotechnology: Legislative action and policymaking in the U.S., 1990–2010. (30th July 2015) - Harris, Rebecca C.
Abstract : This article reviews biotechnology legislation in the 50 states for 11 policy areas spanning 1990–2010, an era of immense growth in biotechnology, genetic knowledge, and significant policy development. Policies regarding health insurance, life insurance, long-term care insurance, DNA data bank collection, biotech research protection, biotech promotion and support, employment discrimination, genetic counselor licensing, human cloning, and genetic privacy each represent major policy responses arising from biotechnology and coinciding with key areas of state regulation (insurance, criminal justice, economic development, labor law, health and safety, privacy, and property rights). This analysis seeks to answer three questions regarding biotechnology legislation at the state level: who is acting (policy adoption), when is policy adopted (policy timing), and what is policy doing (policy content). Theoretical concerns examine state ideology (conservative or liberal), policy type (economic or moral), and the role of external events (federal law, news events, etc.) on state policy adoption. Findings suggest ideological patterns in adoption, timing, and content of biotech policy. Findings also suggest economic policies tend to be more uniform in content than moral policies, and findings also document a clear link between federal policy development, external events, and state policy response.